Using E-Learning Tools to Enhance Students- Mathematicians' Competences in the Context of International Academic Mobility Programmes - Alexander P. Snegurenko; Sergey A. Sosnovsky; Svetlana V. Novikova; Rouzilya R. Yakhina; Natalia L. Valitova; Elmira Sh. Kremleva (National Research Mordova State University, 2019)
Introduction. The article is concerned with the use of special electronic teaching tools to increase the students' understanding of the subject and adaptation to the professional language environment of the host country, taking into account the mathematical education. Our purpose is to develop a methodology of multilingual support of mathematical courses in the host country to improve the effectiveness of students' academic mobility using e-learning tools. Materials and Methods. The basis of the research was methods of system analysis and descriptive and analytical methods, primarily experimental. To identify advantages of the proposed approach the methods of empirical research were used (observation and comparison). To prove the efficiency, classical methods of measurement were used. Results. We analyzed the existing electronic learning environments and defined an e-learning environment Math-Bridge that allows for creating mathematical courses in several languages in parallel. For example, the e-training course "Optimization Methods" was developed in three languages for training Russian-speaking Master programme students. The comparative analysis of the target and control student's groups showed that 100 % of the students in the target group achieved an excellent level of mastering competencies, while the control group has only 75 %. For the control group, the degree of motivation to mathematical studying has not virtually changed (increase by 0,86 %). In the target group the level of student interest to the mathematics increased from 0,9 % to 8,9 % (mean 2.21 %). Discussion and Conclusion. The results described in the article will be useful for the staff of international departments, administrations and deans, as well as teachers of those universities that participate in the students' international academic mobility programmes.